Effects of postactivation potentiation warm-up in male and female sport performances: A brief review. - DeRenne, C. (Strength and Conditioning Journal, 2010)
A proper precompetitive warm-up during sprint competition with explosive athletes will elicit a postactivaton potentiation (PAP). This article will review the effects of heavy warm-up protocols eliciting PAP with explosive male and female athletes, resulting in enhanced performance and provide strength coaches with practical applications.